Discrepancy in prevalence of Huntington's disease in two Swedish regions. (9th April 2017) - Roos, A‐K.; Wiklund, L.; Laurell, K.
Abstract : Background: Huntington's disease (HD) is a neurodegenerative disease with an autosomal dominant pattern of inheritance. The prevalence varies between different geographical regions with an estimated average in Europe of about 6/100 000. Parts of northern Sweden are known to have an accumulation of HD, but no prevalence studies have been undertaken for 50 years. Object: The aim of this study was to estimate the prevalence of HD in the two different Swedish counties of Jämtland and Uppsala and compare them with the reported prevalence in Europe. Method: Patients registered with the diagnosis of HD were identified through medical records in each county. Presymptomatic patients were excluded. We also compared the annual number of individuals with HD registered in the database of the National Board of Health and Welfare in these regions, with all of Sweden. Results: The prevalence of HD was found to be 22.1/100 000 in Jämtland and 4.9/100 000 in Uppsala county. The mean age was 62.2 years and 61.8 years, respectively. The annual average of patients with HD registered at inpatient care was 1.5/100 000 in Jämtland, 0.44/100 000 in Uppsala county, and 0.56/100 000 in all of Sweden. Conclusion: The prevalence of patients with the diagnosis of HD is four times higher in the county of Jämtland than in the county of Uppsala, where the prevalence is more similar to the average in Europe. Our results support earlier findings of regional variations of HD prevalence with an accumulation in certain parts of northern Sweden.